(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The history and the philosophy of teaching methodology bring to light, the importance of speaking skills. The author adopts a communicative approach for the enhancement of speaking skills of her students in the class. The researcher focuses on the philosophy of the teaching methodology processes involved in the conversational interaction of the students, thereby conducting such activities in the class which enable her students to be able to use the language appropriate to given social context. The teacher’s task is to focus the students’ attention, and provide exercises to help them develop language facility; however, to ensure their self-reliance, the teacher should only help the students as much as is strictly necessary.